Development of Learning Devices Using Creative Problem Solving (CPS) Models on Static Electricity Material - Inriani Inriani; Azhar Azhar; Muhammad Nasir (Postgraduate, University of Mataram, 2021)
The learning tools developed are science learning tools using creative problem solving models on static electricity material in the ninth grade of junior high school, in the form of lesson plans, student worksheet and test instruments. The purpose of this research is to produce science learning products with creative problem solving models that are valid and suitable for use in school. The data analysis technique in this study used descriptive analysis, by calculating the validation score for each assessment indicator. The results showed that the value of the validity of science learning tools using creative problem solving models was declared valid with an overall average score of 4.44 very valid categories. Likewise, the empirical validity of the test instrument obtained valid results for each item and was reliable at a value of 0.844 in the high category